Adult ADHD and romantic relationships: What we know and what we can do to help. (9th January 2021) - Wymbs, Brian T.; Canu, Will H.; Sacchetti, Gina M.; Ranson, Loren M.
Abstract: It has been widely maintained that enduring and healthy romantic relationships are critical to quality of life in adulthood, and can buffer the impact of adversity, including psychological disorder. Unfortunately, much research points toward adults with attention‐deficit hyperactivity disorder (ADHD) having short‐lived and discordant romantic relationships. Despite this ample evidence, relatively little research has focused on identifying specific factors that may strengthen or explain their relational difficulties, which would have obvious relationship distress prevention and intervention implications. The current study reviews the state of the literature on romantic relationships in adults with ADHD, including differences that have been established between ADHD and non‐ADHD populations as well as distal and proximal factors that appear to increase risk of relationship distress of adults with ADHD. Finally, notable gaps in the literature are identified and implications are raised with regards to prevention and intervention efforts designed to address functional impairment in adults with ADHD.